Autophagy-mediated regulation of phytohormone metabolism during rice anther development. (2nd September 2017) - Kurusu, Takamitsu; Koyano, Tomoko; Kitahata, Nobutaka; Kojima, Mikiko; Hanamata, Shigeru; Sakakibara, Hitoshi; Kuchitsu, Kazuyuki
ABSTRACT: Autophagy has recently been shown to be required for postmeiotic anther development including anther dehiscence, programmed cell death-mediated degradation of the tapetum and pollen maturation in rice. Several phytohormones are known to play essential roles during male reproductive development including pollen maturation. However, the relationship between phytohormone metabolism and autophagy in plant reproductive development is unknown. We here comprehensively analyzed the effect of autophagy disruption on phytohormone contents in rice anthers at the flowering stage, and found that endogenous levels of active-forms of gibberellins (GAs) and cytokinin, trans-zeatin, were significantly lower in the autophagy-defective mutant, Os atg7–1, than in the wild type. Treatment with GA4 partially recovered maturation of the mutant pollens, but did not recover the limited anther dehiscence as well as sterility phenotype. These results suggest that autophagy affects metabolism and endogenous levels of GAs and cytokinin in rice anthers. Reduction in bioactive GAs in the autophagy-deficient mutant may partially explain the defects in pollen maturation of the autophagy-deficient mutant, but tapetal autophagy also plays other specific roles in fertilization.